Epistemic Vice and Motivation. (16th April 2018) - Tanesini, Alessandra
Abstract: This article argues that intellectual character vices involve non‐instrumental motives to oppose, antagonise, or avoid things that are epistemically good in themselves. This view has been the recent target of criticism based on alleged counterexamples presenting epistemically vicious individuals who are virtuously motivated or at least lack suitable epistemically bad motivations. The paper first presents these examples and shows that they do not undermine the motivational approach. Finally, having distinguished motivating from explanatory reasons for belief and action, it argues that our epistemic practice of vice attribution supplies evidence in favour of motivational accounts of vice.